CORPORATE GOVERNANCE AND ESG PERFORMANCE: A LITERATURE REVIEW OF MEASUREMENT PROXIES AND EMPIRICAL FINDINGS - Novia rizki; Victoria K. Priyambodo; Tri Hanani; Paradisa Sukma (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to examine the relationship between corporate governance and ESG (Environmental, Social, and Governance) performance by identifying measurement proxies and synthesizing empirical findings from previous studies. The method employed is a narrative literature review of 25 Scopus-indexed journal articles. The governance mechanisms examined include board characteristics, namely board size, board independence, CEO duality, gender diversity, expertise and educational background, as well as ownership structures, including institutional, foreign, family, and state ownership. The results indicate that most governance mechanisms positively affect on ESG performance, particularly gender diversity, board independence, environmental expertise, institutional ownership, and foreign ownership. However, several studies report inconsistent regarding board size, CEO duality, and state ownership. These findings confirm that corporate governance is a critical factor in supporting sustainability strategies and enhancing ESG performance